Highlights of 1982 Survey on Occupational Noise and Hearing Conservation Regulations in Canada - Benwell, D. A. (Canadian Acoustics, 1984)
The Canadian Standards Association Task Force on Occupational Noise conducted a survey on occupational noise and hearing conservation regulation in Canada by sending out a questionnaire in January 1982 to 148 representatives of government, regulators, employers, labour, consultants, universities, and hospitals. All representatives were selected due to their interest in the subject. The questionnaire requested information on noise levels, hearing protection, audiometry, warning signs, noise surveys, and workers’ compensation criteria and benefits. As of March 1983, 68 completed questionnaires were returned, and 6 letters sent in lieu of completed